Mycobacterial Control of Host Mitochondria: Bioenergetic and Metabolic Changes Shaping Cell Fate and Infection Outcome - Mohareer, Krishnaveni; Medikonda, Jayashankar; Vadankula, Govinda Raju; Banerjee, Sharmistha (Frontiers in Cellular and Infection Microbiology, 2020)
Mitochondria, is undoubtedly a critical organelle of a eukaryotic cell, which provides energy and offers a platform for most of the cellular signalling pathways that decide cell fate. The role of mitochondria in immune-metabolism is now emerging as a crucial process governing several pathological states, including infection, cancer, and diabetes. Mitochondria have therefore been a vulnerable target for several bacterial and viral pathogens to control host machinery for their survival, replication, and dissemination. Mycobacterium tuberculosis, a highly successful human pathogen, persists inside alveolar macrophages at the primary infection site, applying several strategies to circumvent macrophage defenses, including control of host mitochondria. The infection perse and some mycobacterial factors that enter the host mitochondrial milieu perturb mitochondrial dynamics and function by disturbing mitochondrial membrane potential, shifting bioenergetics parameters such as ATP and ROS, orienting the fate of the cell and thereby infection outcome. In the present review, we attempt to integrate the available information and emerging dogmas to get a holistic view of Mycobacterium tuberculosis infection vis-a-vis mycobacterial factors that target host mitochondria and changes therein in terms of morphology, dynamics, proteomic and bioenergetic alterations that lead to a differential cell fate and immune response determining the disease outcome. We also discuss critical host factors and processes that are overturned by Mycobacterium tuberculosis, such as cAMP-mediated signalling, redox homeostasis, and lipid droplet formation. Further, we also present the gaps and limitations in understanding some of the present research areas which can be further explored and alternate dogmas in understanding some critical processes during Mycobacterium tuberculosis infection and the reasons thereof. Towards the end, we propose to have a set of guidelines for pursuing investigations to maintain uniformity in terms of early and late phase, MOI of infection, infection duration and incubation periods, the strain of mycobacteria, passage numbers and so on which all work as variables and probably different readouts. Such a scenario would, therefore, help in the smooth integration of information towards a better understanding of the disease and identify targets for host-directed therapy.